Acute myocardial infarction in a patient with low cardiovascular risk and elevated lipoprotein (a). Case report - Zacarías-Mendoza, Nathalie Victoria (2022)
Lipoprotein(a) (Lp (a)) is a plasmatic lipid protein complex, which represents a risk factor for atherosclerotic cardiovascular disease (ASCVD). However, conventional lipid assays are unable to measure or estimate Lp (a) and there are no specific therapies approved to substantially reduce Lp (a) concentrations. We report the case of a 49-year-old man with low cardiovascular risk who developed an acute myocardial infarction with ST elevation probably due to elevation of Lp (a) is reported. The purpose of this case report is to highlight the detection and analysis of Lp (a) in the assessment of cardiovascular risk. In addition, current and emerging therapies are described in patients with elevated Lp (a).